Effect of Use of Personal Protective Equipment and Personal Hygiene on Hypertension Incidence in Farmers in Dolok District, North Padang Lawas Regency in 2022 - Hasanal Bolqia Siregar; Sri Malem Indirawati; Rahayu Lubis (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine and analyze the effect of use of personal protective equipment and personal hygiene on hypertension incidence in farmers in Dolok District, North Padang Lawas Regency in 2022. This type of research was an analytical observational with a cross sectional design. The population in this study are farmers who spray pesticides when farming in Dolok District, North Padang Lawas Regency, totaling 9,250 people. This sampling used simple random sampling technique. The sample in this study was 96. This study used multivariate logistic regression analysis. The results showed that use of personal protective equipment and personal hygiene had an influence on hypertension incidence in farmers in Dolok District, North Padang Lawas Regency in 2022.